Dimensions of English language learner autonomy assessment: a systematic review of what is there and what is missing - Liu, Aiju; Abdullah, Amelia; Dong, Hong (Frontiers in Psychology, 2026)
Extensive research highlights the importance of learner autonomy in English language acquisition. Paradoxically, existing assessments for Learner Autonomy in English Language Learning (LAELL) narrowly focus on formal learning environments. This systematic mapping review, identifies frequently used dimensions, and highlights gaps in LAELL assessments within evolving learning contexts. Adhering to PRISMA guidelines, we identified 30 studies (1996–2025) across five databases. Key findings reveal that (1) meta-cognitive dimension is the most frequently addressed in the reviewed studies, followed by motivation and social dimension, while technology, willingness, affective factors, critical thinking, political factors, and self-efficacy are least presented; and (2) adapted questionnaires predominantly originated from older frameworks (50% from 1978–2009), with only 10% since 2016. Three gaps emerge: (1) overreliance on outdated questionnaire adaptations; (2) absence of LAELL assessments designed for informal learning contexts; and (3) insufficient attention to digital competences, particularly technology literacy and critical thinking. These findings highlight a potential misalignment between current assessment tools and contemporary learning environments. We suggest that LAELL assessments be updated to include dimensions of digital competence and critical thinking, and that skill-specific assessments be developed for productive domains like writing.